2021
DOI: 10.3389/fpsyg.2021.649915
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Reluctance in Adopting Open Access Publishing: Insights From a Goal-Directed Perspective

Abstract: Despite growing awareness of the benefits of large-scale open access publishing, individual researchers seem reluctant to adopt this behavior, thereby slowing down the evolution toward a new scientific culture. We outline and apply a goal-directed framework of behavior causation to shed light on this type of behavioral reluctance and to organize and suggest possible intervention strategies. The framework explains behavior as the result of a cycle of events starting with the detection of a discrepancy between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Bührer and Wroblewski (2019) found that "researchers working in an institutional environment that systematically supports the practice of RRI are more active in RRI practices". Köster et al (2021) explain such dynamics as deriving from a mismatch between injunctive and descriptive norms. Descriptive norms are "what most others do", and they contrast with injunctive norms, "what most others approve or disapprove" (Cialdini et al 1990).…”
Section: Open and Responsible Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Bührer and Wroblewski (2019) found that "researchers working in an institutional environment that systematically supports the practice of RRI are more active in RRI practices". Köster et al (2021) explain such dynamics as deriving from a mismatch between injunctive and descriptive norms. Descriptive norms are "what most others do", and they contrast with injunctive norms, "what most others approve or disapprove" (Cialdini et al 1990).…”
Section: Open and Responsible Researchmentioning
confidence: 99%
“…Since, when faced with a clash between injunctive and descriptive norms, people's behaviours tend to follow the latter (Farrow et al 2017), increasing uptake of open and responsible practices faces somewhat of a "collective action problem" (Olson 1971). Köster et al (2021) suggest that a key answer is to alter behaviours through revised incentive structures which bring goals of openness and selfinterest into alignment.…”
Section: Open and Responsible Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the theory of planned behavior to guide adaptation of the OSS survey and provide a lens for understanding researcher intention to engage in open science practices. It has been argued that more holistic assessments of behavior are needed to better understand why some researchers engage in practices and why some do not (Köster et al, 2021;Norris & O'Connor, 2019;Robson et al, 2021). Indeed, given the complexity of behavior change in academia, using theory may help parse out the active ingredients of open science uptake.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The suboptimal behavior (and affect) in mental disorders can be understood as problems in one or more steps of this cycle [15,16]. Aggression (as in impulsive disorders) may be selected as a strategy (assimilation) to solve the discrepancy with a personal goal (e.g., winning an argument), but people may fail to detect that this behavior is itself discrepant with another goal (e.g., to keep their relationship intact).…”
mentioning
confidence: 99%